(untitled) (MAUSAM, 1988)
A reasonably reliable equation was derived (Gupta and Agarwal 1984), relating diffuse sky radiation (Dr) on a horizontal surface to air mass (mr) and Schiiepp turbidity coefficient B in dry atmosphere with constant albedo (A =0.25) of the terrain. The expression for Dr has n corrected for different values of perceptible water w. Also a reasonable equation giving conversion factor for finding Dr (A) from Dr (A=0.25), for different values of air mass mr and water vapour content w has been developed. It has been shown that due to interaction between Band w, within the absorption bands of water vapour, the effect of Band cannot be individually separated.